Admission Blood Glucose and 2-Year Mortality After Acute Myocardial Infarction in Patients With Different Glucose Metabolism Status: A Prospective, Nationwide, and Multicenter Registry - Cui, Kongyong; Fu, Rui; Yang, Jingang; Xu, Haiyan; Yin, Dong; Song, Weihua; Wang, Hongjian; Zhu, Chenggang; Feng, Lei; Wang, Zhifang; Wang, Qingsheng; Lu, Ye; et al. (Frontiers in Endocrinology, 2022)
Background: The prognostic effect of admission blood glucose (ABG) for patients with acute myocardial infarction (AMI) has not been well validated, especially in patients with diabetes. We performed this study to assess the predictive value of ABG for all-cause mortality in AMI patients with different glucose metabolism status. Methods: We evaluated a total of 6,892 AMI patients from the prospective, nationwide, multicenter CAMI registry, of which 2,820 had diabetes, 2,011 had pre-diabetes, and 2,061 had normal glucose regulation (NGR). Patients were divided into high ABG and low ABG groups according to the optimal cutoff values of ABG to predict 2-year mortality for patients with diabetes, pre-diabetes and NGR, respectively. The primary endpoint was all-cause mortality. Results: The optimal cutoff values of ABG for predicting 2-year mortality was 9.0mmol/l, 7.2mmol/l and 6.2mmol/l for patients with diabetes, pre-diabetes and NGR, respectively. Overall, the risk of all-cause mortality in high ABG group was significantly increased compared with that in low ABG group among patients with diabetes (15.2% vs. 8.9%; hazard ratio [HR] 1.787, 95% confidence interval [CI] 1.413-2.260; P<0.0001), pre-diabetes (12.1% vs. 6.1%; HR 2.069, 95%CI 1.518-2.821; P<0.0001) and NGR (11.8% vs. 6.1%; HR 2.009, 95%CI 1.473-2.740; P<0.0001). After the potential confounders were adjusted, high ABG was significantly associated with higher risk of 2-year mortality in patients with diabetes (adjusted HR 1.710, 95%CI 1.327-2.203; P<0.0001), pre-diabetes (adjusted HR 1.731, 95%CI 1.249-2.399; P=0.001) and NGR (adjusted HR 1.529, 95%CI 1.110-2.106; P=0.009). Moreover, adding ABG to the original model led to a slight albeit significant improvement in C-statistic and net reclassification in patients with diabetes and NGR (all P<0.05). Conclusions: This study is the first to demonstrate a strong positive association between ABG and 2-year mortality in AMI patients with diabetes, pre-diabetes and NGR. ABG should be considered as a useful marker for risk stratification in patients with diabetes and NGR. Further randomized trials are warranted to investigate the effects of blood glucose control on the reduction of long-term mortality according to the corresponding ABG thresholds for different glucose metabolism status. Trial registration: ClinicalTrials.gov NCT01874691.